The weak asymptotic solution of the phase field system in the case of confluence of free boundaries in the Stefan-Gibbs-Thomson problem - Danilov, V.G.; Rudnev, V.Yu. (Нелинейные граничные задачи, 2005)
Using the weak asymptotics method, we analyze the confluence of free boundaries in the Stefan-Gibbs-Thomson problem. We construct the global in time solution of the phase field system in this case.